Toward a Critical and Comparative Anthropology of Disability: Absent Presence and Exemplary Personhood. Issue 3 (1st September 2021) - Reno, Joshua; Hart, Kaitlyn; Mendelson, Amy; Molzon, Felicia
Abstract: This article places anthropology in dialogue with critical disability studies (CDS) in order to reassess historical and emerging ethnographic readings of difference. We argue that one unintended consequence of a lack of attention to disability in anthropology, generally, has been an impoverished conception of personhood and power. Building on insights from CDS and the ethnographic literature, we show how non-normative bodies and minds can play a critical role in relationships with non-human others and exemplary persons. Looking beyond hegemonic and secular ideas of disability as a form of misfortune or lack not only offers alternatives for being with disability, in keeping with the aims of CDS, but also shows new directions for comparative discussions of power and difference.